Penggunaan Sistem Informasi Akuntansi Untuk Meningkatkan Pengendalian Siklus Pendapatan - Sulastri Samosir; Aprita Ginting; Riska Harianingsih; Cindy Aulia Rusli; Wanda Dea Khairani; Jufri Darma (Pusat Riset dan Inovasi Nasional, 2025)
The purpose of this study is to analyze the implementation of Accounting Information Systems (AIS) in managing the company's revenue cycle control. The revenue cycle involves a series of crucial activities such as receiving orders, shipping goods, billing, and receiving payments, which require strict supervision to reduce errors and manage existing risks. Without the implementation of AIS, some common problems that often arise in managing the revenue cycle include inaccurate information, loss of employee data archives, difficulty in detecting errors in supervision, as well as limited reporting supervision and invalid data. As a solution, AIS can be implemented to increase data processing capacity, improve storage space, and improve control between parts of the organization. This study investigates the implementation of AIS in recording revenue transactions and its impact on internal control, such as preventing fraud, increasing data accuracy, and accelerating business processes. The results of the study are expected to provide an understanding of how the implementation of AIS can improve revenue cycle control and reduce risks associated with large business transactions.